Economic policy uncertainty and corporate investment: Does quality of governance matter? - Umar Farooq; Mosab I. Tabash; Suhaib Anagreh; Mamdouh Abdulaziz Saleh Al-Faryan (Cogent Economics & Finance, 2022)
A stable economic condition is crucial for an organization's success. Any fluctuation in economic policy directly influences corporate-level decisions. However, exercising better governance can mitigate the adverse effect of such unstable economic conditions. Owing to this, the current research tends to disclose the impact of economic policy uncertainty (EPU) on corporate investment decisions and how this impact varies across countries having better governance quality. To achieve the underlying objective, we use the data for the years 2010-2019 of publicly listed enterprises from 6 Asian economies. The empirical analysis was performed by employing the generalized least square (GLS) and GMM techniques. The statistical analysis reveals an inverse relationship between EPU and corporate investment while a direct relationship between governance quality and corporate investment. In addition to individual impact, better governance quality can mitigate the magnitude of the adverse impact of EPU on corporate investment. Better governance can diversify the negative impacts of EPU by protecting investor rights, eliminating information asymmetric, and enhancing policy stability. Based on empirical analysis, the policy officials are directed to exert efforts for exercising better governance. Similarly, corporate managers are advised to consider the current economic situation while formulating any strategy relating to physical investment. This study is innovative as it reinforces the significance of better governance in disentangling the adverse impacts of EPU on corporate investment.
Keywords: E60; G31; G38; 330; Corporate investment; economic policy uncertainty; GMM; governance quality